Chapter The impact of the US Rebalancing Policy toward Asia Pacific on International Relations in the region - Kasım, Kamer (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
The importance of Asia-Pacific region in United States (US) foreign policy increased in recent years. The US paid special attention to the region during the Obama era declaring the region as a ‘pivot’. The US rebalancing policy has economic, political/diplomatic, and military dimensions aimed to increase the US presence in the region and close cooperation with the US’s allies. The growing influence of China in combination with the South and East China Sea problems led to the US administration coming up with the rebalancing strategy. The US conducted this policy together with its engagement with China. Therefore, China’s perception of the US rebalancing as a kind of containment strategy would not be helpful for the continuation of the strategy. Lack of harmony and disagreements among the US allies in the region challenged the rebalancing policy. The increasing importance of the region in the world economy and the existence of problems in South and East China Sea mean that the US would continue political, economic and military engagement in the region. This paper analyses the main parameters and shortcomings of the US rebalancing strategy in Asia-Pacific and its regional and global implications.